Pengaruh Kepemimpinan Transformasional Terhadap Kinerja Individu Melalui Dukungan Kesehatan Mental: Studi pada Pekerja-Mahasiswa di Bekasi - Aulia Larasati Rahman; Fahmi Ahmad Ferdian; Hafshah Radhiya Yardha; Reva Nabillawati; Satryo Aji Hatmoko; Vera Mita; Yudha Heksa Putra (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study aims to analyze the effect of transformational leadership on individual performance through mental health support among worker-students in Bekasi. The phenomenon of worker-students who simultaneously carry out work and educational responsibilities has the potential to create pressure that affects performance achievement. This study employs a causal quantitative approach using a survey method. Data were collected through questionnaires distributed to 105 respondents selected using a purposive sampling technique. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS 4 software. The results indicate that transformational leadership has a positive and significant effect on individual performance, while mental health support has no significant effect on performance and does not mediate the relationship between transformational leadership and individual performance. The research model explains 21.7% of the variance in individual performance. This study confirms that transformational leadership is the dominant factor in improving the performance of worker-students in Bekasi.